Study on the quenching depth and surface hardness of metal materials by laser quenching variable parameters - Ren, Dongdong; Zhang, Pengjun; Yu, Jiahui; Yao, Yangwu; Li, Xiaoyang (Frontiers in Physics, 2023)
Laser quenching is one of the most outstanding gear tooth surface quenching methods due to its high efficiency, environmental friendliness and performance consistency. Since gear tooth surface laser quenching requires repeated scanning, changing the laser scanning velocity and power by program control can meet the needs of variable depth quenching. The effects of laser scanning velocity and output power on quenching depth and surface Rockwell hardness after quenching were studied and experimental analyzed. The result shows that by adjusting the parameters, the surface hardness of the specimen change a little with the actual received laser energy. However the quenching depth could maintain consistency with laser scanning velocity. The maximum surface Rockwell hardness that a material can achieve by laser quenching depends on the material itself rather than laser power or scanning velocity. Compared with accelerated laser quenching, decelerated laser quenching is more suitable for tooth surface processing.